Influencer Credibility and Content Quality in TikTok Culinary Purchase Decisions - Rudy Haryanto; Ramadhan Pratama; Hairul Anwar (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: This study examines the effects of influencer credibility and TikTok video content quality on culinary purchase decisions in Banjarmasin, Indonesia. It responds to the rapid growth of short-form video marketing and the need for local culinary micro, small, and medium-sized enterprises to promote their products effectively while upholding Sharia-conscious ethical values, particularly honesty, transparency, and trustworthiness.. Method: Using an explanatory quantitative design, data were collected using a structured questionnaire from 103 TikTok users who had viewed culinary promotional content with the goal of having food in their food consumption intentions. The data were analyzed using descriptive statistics, validity and reliability testing, classical assumption testing, and multiple linear regression.. Results: The evidence indicates that influencer credibility has a significant effect on culinary purchasing, with respect to being the strongest of these factors. TikTok video quality has a positive and significant influence too, as it acts to inform and entertain. At the same time, both variables have a significant impact on consumer decision making, yet the limited predictive ability implies the importance of price, taste, halal assurance, accessibility, and the recommendations of peers. Conclusion: The study adds to social commerce and Sharia-informed management literature by showcasing that successful TikTok culinary promotion is not only a factor of visibility, creativity and authenticity, but also that of legitimate communicators, factual sources and a good standard of ethics in content production.